2020
DOI: 10.1002/term.2996
|View full text |Cite
|
Sign up to set email alerts
|

Tubular scaffold with microchannels and an H‐shaped lumen loaded with bone marrow stromal cells promotes neuroregeneration and inhibits apoptosis after spinal cord injury

Abstract: As a result of its complex histological structure, regeneration patterns of grey and white matter are quite different in the spinal cord. Therefore, tissue engineering scaffolds for repairing spinal cord injury must be able to adapt to varying neural regeneration patterns. The aim of the present study was to improve a previously reported spinal cord‐mimicking partition‐type scaffold by adding microchannels on a single tubular wall along its longitudinal axis, thus integrating the two architectures of a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…For example, Chen et al (2020b) showed the regenerative effect of BMSCs seeded into a chitosan tubular scaffold combining the two architectures of a single H-shaped central tube and several microchannels. The scaffold was implanted to bridge the 5-mm defect of a complete transverse lesion in the thoracic spinal cord of rats, and when compared with the empty scaffold, the BMSC enhanced functional improvement and the number of regenerating axons and elicited antiapoptotic effects ( Chen et al, 2020b ).…”
Section: Biomaterials In Combination With Mscs In Sci Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Chen et al (2020b) showed the regenerative effect of BMSCs seeded into a chitosan tubular scaffold combining the two architectures of a single H-shaped central tube and several microchannels. The scaffold was implanted to bridge the 5-mm defect of a complete transverse lesion in the thoracic spinal cord of rats, and when compared with the empty scaffold, the BMSC enhanced functional improvement and the number of regenerating axons and elicited antiapoptotic effects ( Chen et al, 2020b ).…”
Section: Biomaterials In Combination With Mscs In Sci Treatmentmentioning
confidence: 99%
“…For example, Chen et al (2020b) showed the regenerative effect of BMSCs seeded into a chitosan tubular scaffold combining the two architectures of a single H-shaped central tube and several microchannels. The scaffold was implanted to bridge the 5-mm defect of a complete transverse lesion in the thoracic spinal cord of rats, and when compared with the empty scaffold, the BMSC enhanced functional improvement and the number of regenerating axons and elicited antiapoptotic effects ( Chen et al, 2020b ). Peng et al (2018) showed that rat MSCs combined with a nerve-guide collagen scaffold inhibited chronic scar formation, provided linear guidance for the nerves, and promoted M2 polarization to form an anti-inflammatory environment in a hemisected SCI rat model ( Peng et al, 2018 ).…”
Section: Biomaterials In Combination With Mscs In Sci Treatmentmentioning
confidence: 99%
“…This may also explain why the functional recovery was limited while there were a substantial number of regenerating nerve fibers in the present study. Therefore, combinational strategies may be achieved better therapeutic effects, 37 as shown by our group recently 38 …”
Section: Discussionmentioning
confidence: 90%
“…The smoothness and convexity of the scaffold surface can affect protein expression ( Johnson et al, 2018 ). Animal experiments have shown that the scaffold morphology can promote cell migration and axon regeneration ( Chen et al, 2020 ). Currently, most research on SCI repair is focused on modifying traditional hydrogels, and efforts to further strengthen the therapeutic effect of hydrogels, promote the regeneration of nerve stumps, and rebuild neural circuits should focus on modifying traditional hydrogels and developing new hydrogels with optimized mechanical properties, drug encapsulation and sustained release activities, and the ability to load cellular molecules and drugs ( Xu et al, 2013 ; Ucar et al, 2021 ; Yao et al, 2021 ).…”
Section: Characteristics Of Hydrogelsmentioning
confidence: 99%